Complaint Handling and Satisfaction Effects on OTA User Retention in Indonesia - Indriyani, Susi; Silvia, Dewi; Hasbullah, Hasbullah (Annals of Management and Organization Research, 2026)
Purpose: This study aimed to investigate the impact of complaint handling service quality and user satisfaction on customer retention within Indonesia's Online Travel Agent (OTA) industry. Research Methodology: A quantitative survey was conducted, collecting data from 160 OTA users with complaints. The data were analyzed using multiple linear regression to assess the relationships between complaint handling and satisfaction and user retention. Results: The results show that both complaint handling service quality (? = 0.579) and user satisfaction (? = 0.647) significantly and positively affect user retention, explaining 53.4% of its variance (Adj. R² = 0.534, p < 0.001). Effective complaint handling and high satisfaction levels are critical for sustaining customer loyalty. Conclusion: The study concludes that OTAs must prioritize transparent complaint management, empathetic customer service, and personalized satisfaction programs to enhance user retention. These factors contribute significantly to maintaining customer loyalty in the competitive digital tourism market. Limitations: The study is limited by the use of snowball sampling, which affects generalizability. It also relied on self-reported data, which may have introduced bias. Future research could employ mixed-methods designs and expand to cross-cultural contexts. Contributions: This study contributes to the digital service recovery literature by integrating complaint handling and satisfaction factors to explain OTA user retention in Indonesia, offering new insights into the strategic importance of service recovery for customer loyalty.